The Use of Google Classroom in Learning English at the Eleventh Grade at SMKN 1 AMPEK ANGKEK - Anggraini, Mona; Syahrul, Syahrul (Faculty of Education and Teacher Training of IAIN Palopo, 2021)
The purposes of this study were to find out what were students’ difficulties in using Google classroom and how the teacher describe usage Google Classroom in learning English. In this research, the researcher used a qualitative approach, in the form of descriptive qualitative. The informants of this study were students from grade 11th TB 1. The data was got by online observation and interview. The results of the study showed that students’ difficulties in using Google Classroom that were the students had difficulty in uploading videos through Google Classroom, it was caused by the students confused when uploading video through Google Classroom. Then, the students were incorrect in sending assignments in Google classroom, because the students are difficult to upload assignments correctly. Furthermore, the teacher only usage Feature about the assignment in Google Classroom such as giving assignment, material, direction, and deadline. Meanwhile, the teacher didn’t use many features in Google classroom based on their function such as Announcement, Google Calendar, Question, Quizzes, discussion, and grading assessment. Thus, the teacher only used feature related assignments and material, while there were many features in Google Classroom which the teacher did not use based on their function.